Robust Trajectory Tracking Control for Variable Stiffness Actuators With Model Perturbations - Guo, Zhao; Sun, Jiantao; Ling, Jie; Pan, Yongping; Xiao, Xiaohui (Frontiers in Neurorobotics, 2019)
Variable Stiffness Actuators (VSAs) have been introduced to develop new-generation compliant robots. However, the control of VSAs is still challenging because of model perturbations such as parametric uncertainties and external disturbances. This paper proposed a nonlinear disturbance observer (NDOB)-based composite control approach to control both stiffness and position of VSAs under model perturbations. Compared with existing nonlinear control approaches for VSAs, the distinctive features of the proposed approach include: 1) A novel modeling method is applied to analysis the VSA dynamics under complex perturbations produced by parameter uncertainties, external disturbances, and flexible deflection; 2) A novel composite controller integrated feedback linearization with NDOB is developed to increase tracking accuracy and robustness against uncertainties. Both simulations and experiments have verified the effectiveness of the proposed method on VSAs.